2006
DOI: 10.1088/1126-6708/2006/07/011
|View full text |Cite
|
Sign up to set email alerts
|

String theory dual of the β-deformed gauge theory

Abstract: We consider the AdS/CFT correspondence between the β-deformed supersymmetric gauge theory and the type IIB string theory on the Lunin-Maldacena background. Guided by gauge theory results, we modify and extend the supergravity solution of Lunin and Maldacena in two ways. First we make it to be doubly periodic in the deformation parameter, β → β + 1 and β → β + τ 0 , to match the β-periodicity property of the dual gauge theory. Secondly, we reconcile the SL(2, Z) symmetry of the gauge theory, which acts on the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We note that this semi-classical field theory result is valid for any value of the parameters γ i and, as such, can be interpreted [16] as a (weak-coupling) prediction for the τ field in the exact string theory background. The supergravity regime is reached in the limit of γ i 1 which gives:…”
Section: Jhep09(2006)005mentioning
confidence: 54%
See 1 more Smart Citation
“…We note that this semi-classical field theory result is valid for any value of the parameters γ i and, as such, can be interpreted [16] as a (weak-coupling) prediction for the τ field in the exact string theory background. The supergravity regime is reached in the limit of γ i 1 which gives:…”
Section: Jhep09(2006)005mentioning
confidence: 54%
“…Much has been learnt recently about the gauge theory -string theory duality by investigating how the AdS/CFT correspondence [1] is realised when the N = 4 supersymmetric gauge theory is deformed by exactly marginal operators [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Since the gauge theory stays conformal it is expected to be dual (in the appropriate limit) to a supergravity solution with Anti-de Sitter geometry.…”
Section: Introduction and Discussion Of Resultsmentioning
confidence: 99%
“…One way to start an exploration is to consider the string background in [13,19] for the q-deformed case, but the background there seems only valid for q close to one. In another article, some changes were suggested that could possibly extend the validity to arbitrary q values [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in the non-supersymmetric deformation the so(6) bosons do not form a closed subsector but mix with the fermions. Another possibility is that the background itself needs to be corrected, perhaps along the lines of [76]. It is also interesting that the nonsupersymmetric deformation is unstable due to the flow of double trace couplings [77], similar to the case found for orbifolds of N = 4 SYM [78,79].…”
Section: Discussionmentioning
confidence: 99%